Repositioning HR Audit as a Strategic Governance Mechanism: A Conceptual and Regulatory Analysis in the Banking Sector - Tushar Ranjan Barik; Chandra Bhooshan Singh; Rakshak Bharti (Involvement International Journal of Business, 2026)
HR audits are commonly treated as compliance routines rather than strategic governance tools. This study repositions HR audit as a mechanism that links HR alignment, compliance governance, employee retention, and organizational effectiveness. The study adopts a conceptual research design based on a systematic review of HR audit and SHRM literature, combined with a doctrinal analysis of labor and governance regulations in India to develop a conceptual model and research propositions. The findings show that HR audit operates sequentially by strengthening HR alignment, reinforcing compliance governance, improving employee retention, and enhancing organizational effectiveness. The study also identifies regulatory fragmentation and the absence of standardized audit frameworks as major constraints, leading to the proposal of a Human Resource Regulatory and Audit Authority of India (HRRAAI). The study integrates SHRM, governance, and institutional theory to explain how HR audit can function as a strategic governance instrument when supported by regulatory standardization. HR audits have significant untapped potential to enhance governance and performance in banks, but this potential can only be realized through institutional and regulatory support.